Peningkatan Yield Secondary Processing di PT âXâ - Wijaya, Valencia; Octavia, Tanti (Jurnal Titra, 2014)
The percentage of unaccountable in the Secondary Processing Department during 2013 (early 2014) is 0.66%. There are three factors that affect that percentage. Those are processed tobacco spillage, tobacco stem, and another factor that has not been identified. The reduction of processed tobacco spillage and tobacco stem will reduce the percentage of unaccountable. Improvements that implemented are providing tools and modify some machines at Feeding to SKM Area, changing Stem Boxâs setting, replacing broken parts from Stem Box, and providing sieving tools. Other improvement is implementing work instruction to prevent the clean processed tobacco spillage become waste. Improvements that implemented had reduced the percentage of unaccountable and had increased the Yield Secondary Processing by 0.13%.